Beamed neutron emission driven by laser accelerated light ions. (29th April 2016) - Kar, S; Green, A; Ahmed, H; Alejo, A; Robinson, A P L; Cerchez, M; Clarke, R; Doria, D; Dorkings, S; Fernandez, J; Mirfayzi, S R; McKenna, P; et al.
Abstract: Highly anisotropic, beam-like neutron emission with peak flux of the order of 10 9 n/sr was obtained from light nuclei reactions in a pitcher–catcher scenario, by employing MeV ions driven by a sub-petawatt laser. The spatial profile of the neutron beam, fully captured for the first time by employing a CR39 nuclear track detector, shows a FWHM divergence angle of ∼ 70 °, with a peak flux nearly an order of magnitude higher than the isotropic component elsewhere. The observed beamed flux of neutrons is highly favourable for a wide range of applications, and indeed for further transport and moderation to thermal energies. A systematic study employing various combinations of pitcher–catcher materials indicates the dominant reactions being d(p, n+p) 1 H and d(d, n) 3 He. Albeit insufficient cross-section data are available for modelling, the observed anisotropy in the neutrons' spatial and spectral profiles is most likely related to the directionality and high energy of the projectile ions.